Knowledge, precautionary actions, and perceived risk of COVID-19 among Indonesian people - Ratih Oktri Nanda; Lolita Lolita; Wiwik Indayati; Ivong Rusdiyanti; Azis Ikhsanudin; Silvia Mareti (Intelektual Pustaka Media Utama, 2021)
Novel coronavirus was first identified in China in December 2019, causing several cases of the new type of pneumonia. The exported cases were found in other countries, including countries in the Southeast Asia region. At the same time, no cases were confirmed in Indonesia. We aimed to assess COVID-19 related knowledge, precautionary actions, and perceived risk among general Indonesian population when there were no confirmed cases in Indonesia. This study was a descriptive cross-sectional study involving 382 participants aged 17 years and above residing in Indonesia. The data was collected through the online questionnaire from February 19th to February 29th 2020. The average score of COVID-19 related knowledge was 88.0%, whereas 83.8% of the participants had a high level of knowledge. The average score of taking precautionary actions was 77.4% and 65.7% had a high level of performance. In terms of the perceived risk of COVID-19, only 11.3% of the participants perceived themselves likely to acquire COVID-19 when compared with other diseases or accidents. The perceived risk of COVID-19 was significantly associated with precautionary action (p<0.05). Perceived risk of COVID-19 was at a low level when there were no confirmed cases. Effective strategies of risk communication are needed to improve precautionary actions to prevent COVID-19.